The Jihad Dimension in the Struggle of the Great Malay Warriors Against the Colonizers in Pahang: (Dimensi Jihad dalam Perjuangan Pahlawan Melayu Menentang Penjajah di Pahang) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2017)
This article discusses the struggle against colonialism in Pahang in relation to the doctrine of Jihad in Islam. The study was carried out using data gleaned from literature and analysed in an inductive, deductive and comparative manner. The results of this study show that there is an element of Jihad in the struggle of the Malay warriors of Pahang to defend their fatherland.This is the result of the strong Islamic influence in Pahang, the presence of ulama (religious scholars), and circumstances of the time.Keywords: struggle, colonialism, Jihad, ulama, Pahang